Health education as a tool for the prevention of cardiovascular diseases in the Elderly Health Care Program (Research, Society and Development, 2020)
Objective: to describe the experience as an academic nursing in health education activities for the prevention of cardiovascular diseases in the elderly. Method: Qualitative study, descriptive of the type of experience reported in a university extension program. Results: The orientations were carried out through playful activities as a health education strategy. As a consequence of the activities promoted, the elderly showed good acceptance in all the proposed actions, besides showing attention and willingness to perform the activities. The elderly were observed to be more likely to develop the complications of the diseases, so they were guided to collaborate in the attention and care. Conclusion: The health education practices are transforming and bring important contributions to gerontological nursing, because they allow a critical-reflexive thinking and contribute to the formation of future professionals committed to act in an assistance model based on scientific evidence and trained to meet the needs of the elderly population that has been growing over the years, presenting a main focus on prevention of cardiovascular diseases.